EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Jaenudin; Hardimansyah; Herwani; Umi Nasikhah (CV. Adiba Aisha Amira, 2026)
The evaluation of Islamic Religious Education (IRE) plays a vital role in assessing the achievement of educational objectives, which focus not only on cognitive aspects but also on affective and psychomotor aspects. This study aims to analyse the implementation of IRE assessment and to identify the constraints and measures for improvement. The method used was a qualitative approach with data collection techniques involving observation, interviews, and documentation. The results of the study indicate that PAI learning evaluation is still dominated by the assessment of cognitive aspects, whilst the assessment of attitudes and religious practices has not been carried out optimally. The challenges faced include limitations in assessment instruments, the timing of implementation, and teachers’ competence in designing authentic assessments. Therefore, there is a need to develop more comprehensive assessment instruments and provide training for teachers so that they are able to carry out thorough and continuous assessment. With appropriate assessment, it is hoped that Islamic Religious Education (IRE) learning can produce students who not only understand religious teachings theoretically but are also able to practise them in daily life.